PENGARUH JOB DEMANDS DAN JOB RESOURCES TERHADAP EMPLOYEE WELL-BEING (STUDI PADA KARYAWAN TETAP YANG MENJALANI WFH PENUH ATAU KOMBINASI WFH DAN WFO DI JABODETABEK) - Tesa Herianti; Meta Andriani (Ibs Press, 2023)
Changes in the work environment of employees from Work from Office (WFO) to Work Form Home (WFH) during the covid-19 pandemic created new conditions for employees, this study aim to determine, the effect of job demands and job resources on employee well-being in permanent employees, who underwent full WFH or a combination of WFH and WFO in JABODETABEK. The data collection method used in this study used an online questionnaire with a sample of 103 respondents, data analysis using structural Equation Model (SEM) based on Partial Least Square (PLS). The result of this study indicates the job demands have no effect on employee well-being for employees who carry out full WFH or a combination of WFH and WFO in JABODETABEK.